Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12934-017-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome engineering of Escherichia coli for constitutive production of salvianic acid A

Abstract: BackgroundSalvianic acid A (SAA), a valuable natural product from herbal plant Salvia miltiorrhiza, exhibits excellent antioxidant activities on food industries and efficacious therapeutic potential on cardiovascular diseases. Recently, production of SAA in engineered Escherichia coli was established via the artificial biosynthetic pathway of SAA on the multiple plasmids in our previous work. However, the plasmid-mediated system required to supplement expensive inducers and antibiotics during the fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…The final engineered strain E. coli BKD13 produced 5.6 g L −1 of salvianic acid A by fed-batch fermentation in 60 h from glucose without any antibiotics and inducers. 71 HpaBC also can convert L-Tyr into L-DOPA, which is an aromatic pharmaceutical employed for the treatment of Parkinson's disease. Munoz et al 72 reported the construction of an E. coli strain with the metabolic capacity for production of L-DOPA from glucose and speculated that the conversion of L-Tyr into L-DOPA catalyzed by HpaBC may be the rate-limiting step.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…The final engineered strain E. coli BKD13 produced 5.6 g L −1 of salvianic acid A by fed-batch fermentation in 60 h from glucose without any antibiotics and inducers. 71 HpaBC also can convert L-Tyr into L-DOPA, which is an aromatic pharmaceutical employed for the treatment of Parkinson's disease. Munoz et al 72 reported the construction of an E. coli strain with the metabolic capacity for production of L-DOPA from glucose and speculated that the conversion of L-Tyr into L-DOPA catalyzed by HpaBC may be the rate-limiting step.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…These promoters have the potential to be independent of the endogenous transcription regulation and function more robustly than those naturally derived ones (Gilman and Love, 2016;Portela et al, 2017). Some synthetic promoters such as the J231 family in the Registry of Standard Biological Parts have gained wide application in gene circuit construction (Qi et al, 2012), tool development (Jervis et al, 2019), chemical production (Meng et al, 2016;Choi et al, 2017;Zhou et al, 2017) and the characterization of biological systems (Pasotti et al, 2012). However, inconsistencies in their transcriptional strength and responses to environmental signals are often encountered (Pasotti et al, 2012;Kosuri et al, 2013;Zucca et al, 2015;Jervis et al, 2019), for which promoters exhibiting high activities in certain conditions might become the weak ones under another context.…”
Section: Introductionmentioning
confidence: 99%
“…It usually takes 120 to 144 h to realize a satisfactory conversion rate of the substrate to target steroid intermediates in the microbes [5,6,25]. However, it only takes about 48 to 72 h in most of other prokaryotic microorganisms [26][27][28]. The long conversion time is primarily attributed to the low permeability of sterol substrates into the cell wall [2].…”
mentioning
confidence: 99%